PREPARING GIRLS FOR FAMILY LIFE ON THE BASIS OF NATIONAL VALUES ENVIRONMENT IN THE FAMILY (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article explores the importance of preparing girls for family life within the context of national values and the cultural environment present in the family. It delves into the methods used for instilling these values, the results of such upbringing, discussions surrounding gender roles, and concludes with suggestions for fostering an environment that harmonizes family life with national values.